The readymade garment industry of Bangladesh - Siddiqi, Hafiz G. A. (Dhaka : University Press Limited, 2004)
Articles on the industry geared for export marketing in the country.
Includes bibliographical references and index.
Donated By Akbar Ali Khan
The university press
Keywords: Clothing trade -- Bangladesh; Export marketing -- Bangladesh; Marketing